The prevalence and impact of migraine and severe headache in the United States: Updated age, sex, and socioeconomic‐specific estimates from government health surveys. Issue 1 (21st December 2020) - Burch, Rebecca; Rizzoli, Paul; Loder, Elizabeth
Abstract: Background and Objectives: Accurate, up‐to‐date estimates of the burden of migraine and severe headache are important for evidence‐based decision‐making about workforce needs and the distribution of health resources. We used data from US government health surveys to report the prevalence, trends, and impact of this condition by age, sex, and poverty status. Methods: We identified the most recent, publicly available summary statistics from the National Hospital Ambulatory Medical Care Survey, the National Ambulatory Medical Care Survey, and the National Health Interview Survey. We extracted and compiled relevant information from each study, with an emphasis on sex, age, and economic‐related statistics. Results: The age‐adjusted prevalence of migraine and severe headache in the United States has remained stable over many years. In 2018, the age‐adjusted prevalence was 15.9% across all adults. The sex ratio also remains stable, with 21% of women and 10.7% of men affected. Migraine continues to be an important public health problem, accounting for roughly 4 million emergency department (ED) visits in 2016, when headache was the fifth most common reason for an ED visit overall and the third most common reason for ED visits in females 15–64. Migraine also accounted for over 4.3 million office visits. Many adults with migraine or severe headaches are disadvantaged. In 2018, for example, roughly 40% of US adults with migraine were unemployed, and a similar proportion were classified as poor or "near poor." Roughly one in five had no health insurance and about a third had a high school education or less. Conclusions: Migraine and severe headaches are a serious public health issue in the United States, with the highest impact in women of childbearing age and those of lower socioeconomic status. Socioeconomic disadvantages also are highly prevalent among those with headaches. The economic consequences of the current coronavirus pandemic are likely to exacerbate all of these inequities. Increased attention to this high impact chronic pain condition, and improved funding for treatment provision and research, are warranted to reduce the future burden of disease.